Challenges and Opportunities in Online Learning Amid COVID-19: A Study on Hearing–Speech Impaired Students of Jammu and Kashmir. Issue 1 (January 2022) - Kotwal, Renu; Chauhan, Gajendra Singh; Ghosh, Swagata
The pandemic is a distressing time for academia. The past 24 months have caused a deeper rift between learning and teaching. Online classes have become necessary overnight, but the transition was not smooth and productive. Moreover, educating students with speech and hearing disabilities online is not similar to those who can hear and speak. The present study explores the challenges of online classes, the struggles of the student–teacher community, and the limitations of technology to make virtual education possible for the hearing–speech impaired students in Jammu and Kashmir. The study also captures some of the possibilities of effective deliverance. Finally, it suggests imperative changes to make online learning accessible, inclusive and meaningful for the hearing–speech impaired community that depends on facial expressions, lip-sync and sign language to learn and communicate. This article encapsulates how accessible and effective online learning is among the hearing–speech impaired students in the region.